Penerapan Aplikasi Mobile Information Karimun Island Menggunakan Ionic Framework - Sucipto, Adi; Kusumodestoni, R. Hadapiningradja; Zyen, Akhmad Khanif; Husen, Muhamad (JTET (Jurnal Teknik Elektro Terapan), 2018)
Karimunjawa is an archipelago in the Java Sea that belongs to the district of Jepara, Central Java. With a land area of approximately 1,500 hectares and waters of approximately 110,000 hectares, Karimunjawa is now developed into a charm of marine parks that began to favor a lot of local tourists and foreign tourism. Karimunjawa has excellent potential such as nature tourism, religious tourism and culinary tourism. Local and foreign tourists desperately need information about the location to be visited. But to find the location of this tour is still scattered in various websites, so it takes a long time to find out the tourist information quickly and precisely. Utilization of the progress of smartphone technology is one solution of this problem. Therefore, this researh aimed to develop an information application based on Android and which provide information of tourism potential in Karimunjawa island, map, favorites, distance of tourist location and review for tourists in the application which is called Karimun Guide Jepara. In the development of the method used this application is Guidelines for Rapid Application Engineering (GRAPPLE) using an ionic framework that is devoted to build mobile hybrid applications with HTML5, CSS and AngularJS. Karimun Guide Development Jepara, data, maps and map locations are incorporated into the firebase databases so that updating apps is easy and fast.Keywords: Tourism Potential, Ionic Framework, Firebase, Android